Defining moments and reminiscences: an anthology of service experience of public servants in India - edited by Prasanna Mishra (Bhubaneswar Prasanna Mishra, 2023)
Defining Moments and Reminiscences(3y (Bis an Anthology of 32 real life stories; edited and published by Prasanna Mishra, former Secretary to Government of India, and contains reflections, reminiscences and defining moments of 30 Public Servants. The sample of Public Servants has been carefully drawn from different disciplines and includes Engineers, Police Officers, Administrators, a Geologist, a Homeopath, a Health Administrator, a Rice Breeder, Educationists, Forest Officers and a mineral administrator. Some writings in the Anthology are of public servants who are no more. Other contributors have warmly responded to the Editor$1 (Bs request to be part of the venture. The writings reveal the complexities of situations public servants work in, lessons they draw, the way they handle situations and render public service. To some extent, the Anthology demystifies the role Public Servants perform, mostly away from limelight.s
Keywords: IAS as an editor; Reminiscences; Anthology